Leadership, Teamwork, and Collaboration: The Lived Experience of Conducting Multisite Research Focused on Quality and Safety Education for Nurses Competencies in Academia. Issue 2 (March 2021) - Schuler, Monika S.; Letourneau, Rayna; Altmiller, Gerry; Deal, Belinda; Vottero, Beth A.; Boyd, Teri; Ebersole, Nancy W.; Flexner, Randi; Jordan, Janet; Jowell, Vicki; McQuiston, Linda; Norris, Tommie; et al.
Abstract: AIM: The aim of this study was to explore facilitators and barriers to conducting a multisite national study in nursing academia unsupported by grant funding. BACKGROUND: Scholarship focused on the Quality and Safety Education for Nurses (QSEN) competencies stimulates opportunities for research and collaboration among nurse educators and clinicians. Twelve members of the QSEN Academic Task Force collaborated on a multisite study of the effectiveness of a QSEN teaching strategy and published the findings. METHOD: A descriptive phenomenological reflective approach using Kim's critical reflective inquiry model was used to explore the lived experiences of the original study investigators. Data were analyzed using Colaizzi's phenomenological reduction. RESULTS: Findings revealed seven facilitators and one overarching barrier to conducting academic research projects of this scope. CONCLUSION: Participants found that strong leadership, a commitment to teamwork and collaboration, and a shared interest were critical to conducting a successful national study across academic settings.